Proposed Integrated O2O Strategy to Bridge the Sensory Gap: A Case Study of Aldiva - Wahyu Indra Pratama (Journal of Economics and Business UBS, 2026)
The rapid growth of the digital economy has transformed Indonesia’s modest fashion retail landscape. While e-commerce provides convenience and market access, it creates a sensory gap—consumers’ inability to touch, feel, or try products before purchase. For SMEs like Aldiva, this heightens perceived risk, causing purchase hesitation and cart abandonment. Despite dual physical and digital channels, Aldiva’s operations remain siloed, failing to support customer webrooming (online search, offline purchase) due to inventory disconnections and misalignment. This study identifies internal/external drivers of Aldiva’s performance, assesses readiness, and formulates an integrated O2O strategy to bridge the sensory gap: a case study of Aldiva. Using a qualitative explanatory sequential single case study design grounded in the stimulus–organism–response (S–O–R) framework, data came from semi-structured interviews with management and digitally active consumers, revealing operational silos and manual inventory as key hindrances amid rising webrooming opportunities. Aldiva holds high asset value via physical stores but low operational readiness. The proposed integrated online-to-offline (O2O) commerce strategy features real-time inventory integration, incentive alignment, and a secure click-and-collect (pick-up and fit) model. This positions stores as experience hubs, reduces risk, and builds sustainable competitive advantage.